Physical activities of people with visual impairment and their determining factors - Stanimirov, Ksenija; Grbović, Aleksandra; Dimoski, Sanja; Jorgić, Bojan (Specijalna edukacija i rehabilitacija, 2020)
Introduction. Physical activities are very important for physical and mental health and for the quality of life itself. Engaging in them leads to a higher level of participation in community life at any age. However, regardless of their beneficial effects, people with disabilities most often do not meet the minimum physical engagement recommended for a healthy lifestyle. Objective. The aim of the paper was to detect factors related to physical activity of young people with visual impairments. Methods. The sample included 45 adults of both genders (53% of females), ages 18 to 39 (M = 28.78, SD = 7.22), with no additional difficulties that could limit exercising. Physical activity barrier scale for persons who are blind and visually impaired was used. Results. The results showed that visually impaired participants most often faced unfavorable environmental factors when engaging in physical activity, as well as barriers arising from the physical environment. This is followed by personal factors, where psychological barriers were expressed. Factors related to visual impairment were in the third place. The variables important for participation of young adults in physical activities were gender and independent movement, while the degree of visual impairment and working status were not important. Compared to males, females experienced four out of eight examined barriers significantly more often, while persons with impaired vision who do not move independently experienced a significantly higher frequency of the three types of tested barriers. Conclusion. The research findings imply that in order to increase the level of participation of people with visual impairments in physical activities, society must first strive for greater adaptation to the physical and social environment.
Keywords: visual impairment, physical activities, barriers, environmental factors, personal factors